Build it the rebel playbook for world class employee engagement - Elliott, Glenn 1972-; Corey, Debra (Wiley, 2018)
"The current way of treating people at work has failed. Globally, only 30% of employees are engaged in their jobs, and in this fast-paced world that's just not enough. The world's best companies understand this, and have been quietly treating people differently for nearly two decades. Now you can learn their secrets and discover The Engagement Bridge[trademark] model, proven to build bottom line value for companies through sustainable employee engagement. Companies with the best cultures generate stock market returns of twice the general market and enjoy half the employee turnover of their peers. Their staff innovate more, deliver better customer service and, hands-down, beat the competition. These companies outperform and disrupt their markets. They break the rules of traditional HR, they rebel against the status quo. Build it has found these rebels and the rulebreakers. From small startups to global powerhouses, this book shows that courage, commitment, and a people-centric mindset, rather than money and resources, are what you need to turn an average business into a category leader. The book follows the clear and proven Engagement Bridge[trademark] model, developed from working with thousands of leading companies worldwide on their own employee engagement journeys. The practical model highlights the areas that leaders need to examine in order to build a highly engaged company culture and provides a framework for success. Build it is packed with tips, tools and real-life examples from employers including NASDAQ, Unilever, IBM, KPMG, 3M, and McDonald's to help you start doing this not tomorrow, but today. Readers will learn: How employee engagement helps companies perform The key factors that drive engagement, and how they work together What the world's most rebellious companies have done to break the rules of traditional HR and improve engagement How to implement The Engagement BridgeTM model to boost productivity, innovation, and better decision-making Unique in this category, Build it is written from two sharply different perspectives. Glenn Elliott is a multi-award winning Entrepreneur of the Year, CEO and growth investor. He talks candidly about the mistakes and missteps he has made whilst building Reward Gateway into a USD300m category leader in employee engagement technology. Debra Corey brings 30 years experience in senior level HR roles at global companies such as Gap, Quintiles, Honeywell and Merlin Entertainments. She shares the practical tools and case studies that can kickstart your employee engagement plan, bringing her own pragmatic and engaging style to each situation"--